Perioperative Treatment with Rivaroxaban and Dabigatran on Changes of Coagulation and Platelet Activation Biomarkers following Left Atrial Appendage Closure - Yao Yao; Yanli Li; Qinchun Jin; Xiaoye Li; Xiaochun Zhang; Qianzhou Lv (Cardiovascular Therapeutics)
Insufficient data exist regarding the investigation of the impact of novel oral anticoagulants (NOACs) on coagulation activation biomarkers in the context of left atrial appendage closure (LAAC) and device-related thrombosis (DRT). The study was designed to investigate the changes and presence of coagulation activation biomarkers between different antithrombotic strategies following LAAC. A total of 120 nonvalvular atrial fibrillation patients intolerant of long-term anticoagulants, who underwent successful WATCHMAN closure implantation, were enrolled (rivaroxaban, n=82; dabigatran, n=38). Blood samples were obtained from left atrium (LA) and left atrial appendage (LAA) during the operation and fasting blood samples on the same day of LAAC and 45 days after discharge. The biochemical indicators, thrombin-antithrombin complex (TAT), soluble P-selectin (sP-selectin), von Willebrand factor (vWF), and CD40 ligand (CD40L), were measured by enzyme-linked immunosorbent assay. The primary endpoints of this study were the efficacy and safety characteristics of different antithrombotic strategies, including DRT incidence, stroke or transient ischemic attack, systemic embolism, and clinical major and nonmajor bleeding complications during the follow-up of 180 days. The results revealed that TAT, vWF, sP-selectin, and CD40L levels in vein were significantly reduced by 2.4% (p=0.043), 5.0% (p<0.001), 8.7% (p<0.001), and 2.5% (p=0.043) from their baseline levels after rivaroxaban treatment. Conversely, no significant changes were detected in the dabigatran group. Furthermore, the plasma levels of platelet activation biomarkers (CD40L and sP-selectin) in both LA and LAA groups were significantly lower after anticoagulation with rivaroxaban, as compared to dabigatran treatment (CD40L: 554.62±155.54 vs. 445.02±130.04 for LA p=0.0013, 578.51±156.28 vs. 480.13±164.37 for LAA p=0.0052; sP-selectin: 2849.07±846.69 vs. 2225.54±799.96 for LA p=0.0105, 2915.52±1402.40 vs. 2203.41±1061.67 for LAA p=0.0022). Notably, the present study suggests that rivaroxaban may be more effective in the prevention of DRT for patients undergoing LAAC.